2019
DOI: 10.1021/acsami.9b09935
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Titanium Dioxide Surface Defects on the Interfacial Composition and Energetics of Evaporated Perovskite Active Layers

Abstract: This investigation elucidates critical Brønsted and Lewis acid–base interactions at the titanium dioxide (TiO2) surface that control the interfacial composition and, thus, the energetics of vacuum-processed methylammonium lead iodide (MAPbI3) perovskite active layers (PALs). In situ photoelectron spectroscopy analysis shows that interfacial growth, chemical composition, and energetics of co-deposited methylammonium iodide (MAI)/PbI2 thin films are significantly different on bare and (3-aminopropyl)­triethoxysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(79 citation statements)
references
References 46 publications
13
66
0
Order By: Relevance
“…This goes beyond previous studies, where detailed investigations showed that the substrate material can influence the composition and electronic structure of the perovskite thin film close to the underlying charge transport layer. [65][66][67][68] However, the present study supplements these findings by highlighting that, beyond the crystallization during the initial stage of thin-film formation, the incorporation of MAI into the perovskite framework, and thereby the composition of the perovskite, continuous to be influenced throughout the entire thin film.…”
Section: Interplay Between Substrate Materials and Thin-film Formation During Co-evaporationsupporting
confidence: 68%
See 2 more Smart Citations
“…This goes beyond previous studies, where detailed investigations showed that the substrate material can influence the composition and electronic structure of the perovskite thin film close to the underlying charge transport layer. [65][66][67][68] However, the present study supplements these findings by highlighting that, beyond the crystallization during the initial stage of thin-film formation, the incorporation of MAI into the perovskite framework, and thereby the composition of the perovskite, continuous to be influenced throughout the entire thin film.…”
Section: Interplay Between Substrate Materials and Thin-film Formation During Co-evaporationsupporting
confidence: 68%
“…However, compositional differences in the very first atomic layers (absorber thicknesses below 5 nm) as investigated in detail by Olthof et al and others may still be present. [65][66][67][68] The density of initial nuclei is relatively large, with several nuclei being present with areas of a few 100 × 100 nm 2 in this stage. In particular, for SnO 2 substrates that exhibit slightly larger grain sizes compared to the other substrate materials in the early phase of the perovskite thin-film formation, a Volmer-Weberlike island growth mode for co-evaporated thin films can be concluded from the individual crystallites forming at this stage.…”
Section: Basic Crystallization Model For Co-evaporated Perovskite Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, as described by Boyd et al, this reaction, which is not specific to NiO x , can happen with other metal oxides and has been reported with TiO 2 and SnO 2 . [ 32–34 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 8,9 ] Moreover, the unique surface chemistry of oxide semiconductors has recently been demonstrated to induce interfacial perovskite decomposition via chemical reactions (like redox reactions and acid–base reactions), thus unfavorable to interfacial charge extraction as well as long‐term stability. [ 10–14 ]…”
Section: Introductionmentioning
confidence: 99%